DOI: 10.31274/etd-180810-1392
|View full text |Cite
|
Sign up to set email alerts
|

Pursuing a proxy for carbon cycling in the temperate North Atlantic: Investigation of the utility of Arctica islandica shell carbonate to millennial-scale dissolved inorganic carbon reconstructions

Abstract: Introduction Materials and Methods Results Discussion Conclusions provided me with the will, the means, the motivation and the courage to undertake this, and every, adventure of my life. Mom,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 96 publications
(98 reference statements)
1
6
0
Order By: Relevance
“…The average source amino acid  15 N value for the periostracum sample taken from shell DMC was 5.7‰. This compares very well to the average  15 N of the sediment collected from Tank A (in which shell DMC grew) throughout the experiment, which was also 5.7‰ (Supplementary Table 2; Beirne, 2011). These values are slightly higher than those measured in the adductor muscle sample from the same clam, which averaged 4.3‰, although these values are still within 2 average analytical uncertainty of each other.…”
Section:  15 N Of Amino Acidssupporting
confidence: 68%
See 3 more Smart Citations
“…The average source amino acid  15 N value for the periostracum sample taken from shell DMC was 5.7‰. This compares very well to the average  15 N of the sediment collected from Tank A (in which shell DMC grew) throughout the experiment, which was also 5.7‰ (Supplementary Table 2; Beirne, 2011). These values are slightly higher than those measured in the adductor muscle sample from the same clam, which averaged 4.3‰, although these values are still within 2 average analytical uncertainty of each other.…”
Section:  15 N Of Amino Acidssupporting
confidence: 68%
“…The long term, average, 2 analytical uncertainty was ±1.9‰ based on the standards run throughout the sampling period. In order to analyze the extent to which the periostracum  15 N reflects the  15 N of its food source, we compared the average  15 N of the source amino acids of the periostracum sample from the shell collected from Tank A at the Darling Marine Center to the average  15 N of the sediment samples taken from this tank and reported in Beirne (2011). Sediment samples were taken from the top 0.5 cm of sediment in 10 different flower pots positioned in this tank, with care taken to avoid any clam excrement present.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weidman (1995) demonstrated that the geochemical signature in the shell material reflects that of the ambient water conditions and not pore water. Arctica islandica is highly suitable for environmental and ocean studies because (1) A. islandica is extremely long-lived -up to 5 centuries (Butler et al, 2013;Schöne et al, 2005;Wanamaker Jr. et al, 2008a); (2) it produces annual growth increments in its shell (Jones, 1980); (3) regional increment series can be crossdated, demonstrating a common response to environmental forcing(s) (Schöne et al, 2003); (4) fossil shells can be crossdated and floating shell chronologies can be constructed after radiocarbon dating (Scourse et al, 2006); (5) live-caught shells can be crossdated with fossil shells to assemble very long, absolutely dated growth records (Butler et al, 2009(Butler et al, , 2011Marchitto et al, 2000); (6) master shell chronologies can be created that are as statistically robust as tree ring chronologies (Butler et al, 2010); (7) it precipitates its aragonite shell in oxygen isotope equilibrium with ambient seawater (Weidman et al, 1994); and (8) the geochemical signature (e.g., 14 C, δ 18 O, δ 13 C) from shell material has been used to reconstruct ocean circulation, hydrographic changes, seasonal changes in ocean conditions, and ecosystem dynamics (Butler et al, 2009;Schöne et al, 2005Schöne et al, , 2011aScourse et al, 2012;Wanamaker Jr. et al, 2008a, b, 2009, 2011Weidman and Jones, 1993;Weidman et al, 1994;Witbaard and Bergman, 2003). Despite the potential as environmental proxies, applications of non-traditional isotopic systems (δ 11 B and δ 88 / 86 Sr) that have the capacity to reveal additional oceanographic and environmental information have not been explored fully.…”
Section: The Biogenic Archive Arctica Islandicamentioning
confidence: 99%